The Role of the South Sumatera Regional Liaison Office of the Judicial Commission in Monitoring the 2024 Simultaneous Regional Elections Towards a Clean Judiciary - Junaidi; M. Martindo Merta; Mila Surahmi; Citra Dewi Saputra; Tri Nugroho Akbar; Patih Ahmad Rafie (Help: Journal of Community Service, 2024)
The simultaneous implementation of national and regional elections in 2024 presents significant challenges for Indonesia's democratic journey, particularly in ensuring a fair, transparent, and corruption-free process. In this context, the role of the South Sumatera Regional Liaison Office of the Judicial Commission is crucial in overseeing the 2024 Simultaneous Regional Elections towards the establishment of a clean judiciary. This office is responsible for monitoring and maintaining the integrity of judicial processes, particularly in resolving any election disputes that may arise. By enforcing strict oversight of judges' conduct and educating the public on the importance of legal awareness, the Judicial Commission Liaison Office strives to ensure that the electoral process aligns with democratic principles of justice. Through outreach, court monitoring, and receiving public complaints, the office actively works to prevent abuses of power and uphold judicial independence. These efforts are expected to enhance the quality of the election administration and strengthen public trust in the judicial system, thereby creating a conducive and clean legal environment in South Sumatera during the 2024 Simultaneous Regional Elections.